Employee Performance and the Impact of Workplace Facilities and Discipline - Almita; Muh. Tahir; Mu’fidatul Nurul Hajjad (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2023)
The objective of this study was threefold: (i) to examine the impact of work facilities on employee performance at the Human Resources Development Agency of West Sulawesi Province, (ii) to investigate the influence of work discipline on employee performance at the same agency, and (iii) to explore the combined effect of work facilities and work discipline on employee performance at the Human Resources Development Agency of West Sulawesi Province. This study employs quantitative methodologies by gathering data through the administration of questionnaires. The present study was conducted in the Human Resources Development Agency of West Sulawesi Province, encompassing a total population of 43 personnel. The sample for this research was determined using the saturation sampling technique. The data obtained from the questionnaire were subjected to analysis using the SPSS software programme. The findings of the research indicate that there is a noteworthy and favourable impact of work facilities on the performance of employees. This finding demonstrates that the presence of favourable and satisfactory work conditions has a positive impact on employee performance. The adherence to work discipline is found to have a notable and favourable impact on the overall performance of employees. This finding indicates a positive correlation between an employee's work discipline and their performance.